Reflective Supervision Models in School Counseling: A Narrative Review of Approaches and Outcomes - Maya Masyita Suherman; Agus Taufik; Dona Fitri Annisa (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Reflective supervision has emerged as a critical component in the professional development of school counselors, yet a comprehensive synthesis of existing models and their outcomes remains limited. Purpose: This narrative review aims to identify and analyze various reflective supervision models used in school counseling contexts and examine their reported impacts on counselors' professional growth. Methods: A narrative review methodology was employed, analyzing articles published between 2018 and 2024 from Google Scholar and ERIC databases. Search terms included